Decaffeinated Green Coffee Bean Extract Attenuates Diet-Induced Obesity and Insulin Resistance in Mice - Su Jin Song (Evidence-Based Complementary and Alternative Medicine, 2014)
This study investigated whether decaffeinated green coffee bean extract prevents obesity and improves insulin resistance and elucidated its mechanism of action. Male C57BL/6N mice (N=48) were divided into six dietary groups: chow diet, HFD, HFD-supplemented with 0.1%, 0.3%, and 0.9% decaffeinated green coffee bean extract, and 0.15% 5-caffeoylquinic acid. Based on the reduction in HFD-induced body weight gain and increments in plasma lipids, glucose, and insulin levels, the minimum effective dose of green coffee bean extract appears to be 0.3%. Green coffee bean extract resulted in downregulation of genes involved in WNT10b- and galanin-mediated adipogenesis and TLR4-mediated proinflammatory pathway and stimulation of GLUT4 translocation to the plasma membrane in white adipose tissue. Taken together, decaffeinated green coffee bean extract appeared to reverse HFD-induced fat accumulation and insulin resistance by downregulating the genes involved in adipogenesis and inflammation in visceral adipose tissue.